2015
DOI: 10.18632/oncotarget.5382
|View full text |Cite
|
Sign up to set email alerts
|

Application of functional vincristine plus dasatinib liposomes to deletion of vasculogenic mimicry channels in triple-negative breast cancer

Abstract: Standard chemotherapy cannot eradicate triple-negative breast cancer (TNBC) while the residual cancer cells readily form the vasculogenic mimicry (VM) channels, which lead to the relapse of cancer after treatment. In this study, the functional vincristine plus dasatinib liposomes, modified by a targeting molecule DSPE-PEG2000-c(RGDyK), were fabricated to address this issue. The investigations were performed on TNBC MDA-MB-231 cells and MDA-MB-231 xenografts in nude mice. The liposomes exhibited the superior pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In fact, an in vitro model using liposomes showed that both drugs can cause cell death and inhibition of vessel formation in MDA-MB-231 cells grown in matrigel. In addition, the use of these liposomes decreases the tumor volume of xenografts in nude mice (68). The authors also demonstrated that the use of liposomes for transporting compounds with different targets, such as epirubicin (a DNA intercalant) and celecoxib (a cyclooxygenase 2 inhibitor) are able to inhibit VM in breast cancer cells (69).…”
Section: Vm As a Therapeutic Targetmentioning
confidence: 96%
“…In fact, an in vitro model using liposomes showed that both drugs can cause cell death and inhibition of vessel formation in MDA-MB-231 cells grown in matrigel. In addition, the use of these liposomes decreases the tumor volume of xenografts in nude mice (68). The authors also demonstrated that the use of liposomes for transporting compounds with different targets, such as epirubicin (a DNA intercalant) and celecoxib (a cyclooxygenase 2 inhibitor) are able to inhibit VM in breast cancer cells (69).…”
Section: Vm As a Therapeutic Targetmentioning
confidence: 96%
“…Results showed that the breast cancer cells exhibited the greatest cell shrinkage and nuclear shrinkage after treatment with functional vincristine plus dasatinib liposomes as compared to the controls. As revealed in our previous study [22], the related mechanisms were associated with the activated caspases 8 and 9 in the upstream, followed by the activated caspase 3 in the downstream, resulting in a cascade of apoptotic reactions in cancer cells [32]. …”
Section: Discussionmentioning
confidence: 99%
“…It is known that the secreted MMP-2 and MMP-9 in cancer cells cause hydrolysis of the extracellular matrix, enabling cancer cells to break through the original site into circulation system and finally form the secondary metastatic sites [38]. After treatment with functional vincristine plus dasatinib liposomes, significant downregulation of MMP-2 and 9 could explain the mechanism of preventing the invasion of breast cancer cells [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dasatinib treatment also exerts immunosuppressive effects (Blake, et al 2008; Fraser, et al 2009), which may offset the effects of anti-tumor immunity. More recently, a nanoparticle formulation of dasatinib has been utilized in combination with the anti-microtubule chemotherapy, vincristine, and results indicate 1) enhanced tumor cell uptake of dasatinib, 2) increased apoptosis, and 3) decreased vascular mimicry channels (Zeng, et al 2015). Whether or not nanoparticle delivery of anti-Src siRNA can recapitulate the effects of liposomal dasatinib is unclear.…”
Section: Tnbc Subtype-specific Therapeutic Strategies: What Are the Lmentioning
confidence: 99%